PENGEMBANGAN ECOLOGICAL MONITORING PADA PROGRAM PEMBERDAYAAN MASYARAKAT UNTUK PEREMPUAN MANDIRI DI DESA MEKARMUKTI KECAMATAN CIHAMPELAS KABUPATEN BANDUNG BARAT - Febriyanty, Herda; Marjuki, Marjuki; Aribowo, Aribowo (Jurnal Ilmiah Kebijakan dan Pelayanan Pekerjaan Sosial (Biyan), 2024)
Poverty is an issue that is consistently discussed and debated in various forums, so that poverty alleviation carried out by the Indonesian Government in the last decade has been realized through programs from various sectors. One of the programs implemented in the context of poverty alleviation is community empowerment. The aim of this research is to find out and improve the design of Ecological Monitoring in Community Empowerment Programs for Independent Women. The method used in this research is a qualitative research method. Meanwhile, the research design used by researchers is Participatory Action Research (PAR) using indepth interview, observation, documentation study and FGD data collection techniques. The data sources in this research are primary data sources from community members who take part in community and stakeholder in empowerment programs. Secondary data comes from documentation studies in the form of literature and the results of other people's research. The research results show that ecological monitoring in empowerment programs that consist of PDP Sosial Mandiri Foundation, Keluarga Harapan’s Assistant, the Government of Desa Mekarmukti, community UMKM, entrepreneur and klien can be implemented and is effective for community empowerment to increase active participation from stakeholders as a resource system in the community as well as the preparation of monitoring instruments that can be used when monitoring programs.